Discursive constructions of inclusiveness within the context of 1Malaysia in the 10th Malaysia Plan 2010-2015 / Mary Varghese - Varghese, Mary (2015)
This study examines the discursive construction of inclusiveness in the context of 1Malaysia, a signifier of unity and identity, launched in 2009 by the 6th Prime Minister, Najib Razak. This blueprint may be seen as a political response to social and political discord as well as economic challenges that led to political losses for the ruling government in the General Elections of 2008. Set within the context of political economy, and in particular, the development agenda 2010-2015 as laid out in the 10th Malaysia Plan, the study probes the means by which the constructions of inclusiveness negotiates the differing and sometimes conflicting demands of inclusiveness. Issues of identity and inclusiveness have been central preoccupations for Malaysia since Independence from Britain in 1957. This is evidenced by the various state-led discourses of nation-building such as the New Economic Policy of (NEP), Vision 2020, Islam Hadhari as well as the current project of 1Malaysia, all introduced by different prime ministers from the ruling party that has held power since independence. The ethnic riots of 1969 led to the introduction of ethnic-based affirmative action policies premised on establishing an equitable society, an important criterion for unity. However, 45 years since the riots, researchers, studies as well as government documents such as the Government Transformation Programme (GTP) as well as the New Economic Model (NEM) of 2010 indicate that in addition to inter-ethnic inequalities, intra-ethnic, spatial and class inequalities are becoming more apparent in the country. While the GTP as well as the NEM have highlighted the problems that the country is facing, it is the 10th Malaysia Plan that proposes solutions through policies that the government intends to implement. The overarching principle guiding these plans and proposals is that of 1Malaysia. However, vagueness of the concept as well as the pressure from right-wing groups have been indicated as hindrances to fully realising the inclusiveness of 1Malaysia asserted in Prime Minister Najib Razak’s early speeches and other documents. Against this background, the study seeks to understand the means by which the discourse of the Plan builds inclusiveness. Specifically, the study is focused on the means by which civic, ethnic, economic and social inclusiveness is constructed as well as the contexts of their occurrence. The use of discourse as an element of social practice is the central preoccupation of this study. This focus on discourse is complemented with an examination of the social context in which the discourse constructs notions of such inclusiveness. Therefore, employing a micro-level examination of social actors, verb processes and modality within the paradigm of Critical Discourse Analysis (CDA), the study seeks an understanding of the means by which the institutional discourse of the 10th Malaysia Plan accommodates the many and varying calls for inclusiveness and change. The study seeks to understand the extent to which 1Malaysia as the new blueprint actualises the change and inclusiveness apparent in texts such as the Prime Minister’s speeches, the GTP, the NEM and opinion editorials in the New Straits’ Times, all stressing social and economic reforms. Findings suggest that authority discourse is layered. On the one hand, the need for a future-focussed pragmatism in issues of economy is apparent. This is found side by side with attempts to foster an equitable social justice and a sense of belonging for all Malaysians. At the same time, the need to accommodate past practices and orientations are also stressed. The accommodation of these, oftentimes contradictory orientations in the discursive construction of 1Malaysia point to instrumental inclusiveness, oriented to specific audiences. The findings may raise questions regarding the nature of inclusiveness being introduced, the purposes of their introduction as well as the extent to which the construction of inclusiveness within the 10th Malaysia Plan addresses the needs of the nation.